Independent Reading and the ‘Social Turn’: How Adolescent Reading Habits and Motivation Relate to Cultivating Social Relationships - Matthew Knoester (Networks: An Online Journal for Teacher Research, 2010)
Research suggests that independent reading outside of school is a strong indicator of school and reading success. However, studies also suggest that student recreational reading significantly decreases in the middle school years. This article explores some of the reasons adolescent students choose to read independently or are reluctant to do so. In this teacher research study the author interviewed his former students, their parents, and their current teachers about what motivates adolescents to read or not to read. Evidence from this study suggests that independent reading is intimately connected to various social practices, despite commonly held views that describe independent reading as a solitary activity. Teaching strategies to encourage student motivation are shared.